Identical twins excited to receive degrees together - Nor Salwana, Mohammad Idris (UMPSA, 2023)
GAMBANG, 24 October 2023 – A pair of twins received their degrees together in the same field, namely Bachelor of Electronics Engineering Technology (Computer Systems) and it was a sweet moment for them at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) 18th Convocation Ceremony at the Sports Complex Hall recently.